DNA copy number and structural variation (CNV) contributions to adult and childhood obesity. (29th July 2020) - Phillips, Megan; Babu, Jeganathan Ramesh; Wang, Xu; Geetha, Thangiah
Abstract : In recent years, obesity has reached epidemic proportions globally and has become a major public health concern. The development of obesity is likely caused by several behavioral, environmental, and genetic factors. Genomic variability among individuals is largely due to copy number variations (CNVs). Recent genome-wide association studies (GWAS) have successfully identified many loci containing CNV related to obesity. These obesity-related CNVs are informative to the diagnosis and treatment of genomic diseases. A more comprehensive classification of CNVs may provide the basis for determining how genomic diversity impacts the mechanisms of expression for obesity in children and adults of a variety of genders and ethnicities. In this review, we summarize current knowledge on the relationship between obesity and the CNV of several genomic regions, with an emphasis on genes at the following loci: 11q11, 1p21.1, 10q11.22, 10q26.3, 16q12.2, 16p12.3, and 4q25.